Predicting the effect of headphones on the time to localize a target in an auditory-guided visual search task - Lladó, Pedro; Barumerli, Roberto; Baumgartner, Robert; Majdak, Piotr (Frontiers in Virtual Reality, 2024)
In augmented reality scenarios, headphones obstruct the direct path of the sound to the ears, affecting the users’ abilities to localize surrounding sound sources and compromising the immersive experience. Unfortunately, the assessment of the perceptual implications of wearing headphones on localization in ecologically valid scenarios is costly and time-consuming. Here, we propose a model-based tool for automatic assessment of the dynamic localization degradation (DLD) introduced by headphones describing the time required to find a target in an auditory-guided visual search task. First, we introduce the DLD score obtained for twelve headphones and the search times with actual listeners. Then, we describe the predictions of the headphone-induced DLD score obtained by an auditory model designed to simulate the listener’s search time. Our results indicate that our tool can predict the degradation score of unseen headphones. Thus, our tool can be applied to automatically assess the impact of headphones on listener experience in augmented reality applications.